Previsão de fornecimento de energia elétrica: um estudo de caso do ponto de vista do barramento - Daniela Dias Rodrigues (2002)
Information of energy demand fron minutes or hours ahead is very important to the electrical industrial sector (from utility companies to the national operator of the system, ONS). Having this information, they can manage the energy generated, transmitted and distributed to many points of the grid with better quality and in a optimized way. This partially exolains why load foresting has much attention recently